Land Used Mapping using Unmanned Aerial Vehicle (UAV) along Parit Rasipan Drainage System - Miswan, M S; Hamdan, R; Roffe, N I; Wurochekke, A A (International Journal of Sustainable Construction Engineering and Technology, 2022)
Excess nutrients accelerate the growth of plants and algae in water sources, leading to environmental issues like flow retardation (flood), a decrease in the amount of oxygen in the water, and a decline in the quality of the water. Therefore, the goal of this study is to identify the quality Parit Rasipan drainage system's eutrophic level in terms of temperature, dissolved oxygen, pH, and turbidity; and to analyse an NDVI (Normalized Difference Vegetation Index) image taken by unmanned aerial vehicle (UAV) and using Agisoft photoscan software. As a result, four sampling locations—residential (S1), industrial (S2), agricultural (S3), and farming (S4)—have been chosen for water quality sampling and analysis along the Parit Rasipan drainage system. The HACH method was used to analyse water samples that have been obtained according to the Standard Methods for Water and Wastewater Examinations. It was found that agricultural zone was poor water quality compared residential, industrial and farming zones with measurements of 3.82 mg/L, 3.09, 25.57 °C, and 14.6 NTU, respectively, the agricultural zone has the highest values for the four metrics of dissolved oxygen, pH, temperature, and turbidity. This scenario could be due to the usage of the fertilizer to cultivate the oil palm contributed to Parit rasipan drainage system (S3) which resulted in a substantial amount of eutrophication. Hence, the use of UAVs and the agisoft photoscan programme has considerably improved the mapping of the water quality metrics and eutrophic level.